Associations of sociodemographic, clinical factors and HLA-B alleles with enthesitis and peripheral arthritis in patients with ankylosing spondylitis - Michael H Weisman; John D Reveille; MinJae Lee; Matthew A Brown; Michael Ward; Lianne Gensler; Mariko Ishimori; Amirali Tahanan; Mohammad Hossein Rahbar; Mark Hwang; Benjamin Sornrung Naovarat (RMD Open)
Objectives Factors associated with peripheral arthritis and enthesitis, especially Achilles tendonitis and plantar fasciitis, were examined in a longitudinal cohort of 1075 patients with ankylosing spondylitis (AS) (also known as radiographic axial spondyloarthritis).Methods Patients were derived from the Prospective Study of Outcomes in Ankylosing Spondylitis cohort. Disease activity and functional indices, as well as physical examination and medications used, were measured at every study visit. Univariable and multivariable analyses of the association of peripheral arthritis and enthesitis with clinical, sociodemographic factors were performed. Human leucocyte antigen (HLA)-B alleles were analysed by single-stranded conformational polymorphism analysis.Results Those with peripheral arthritis on examination were more likely to have psoriasis (p=0.001, OR=1.68; CI, 1.11, 2.54), greater functional impairment (p<0.001 OR=1.72; CI, 1.31, 2.27), higher erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) levels (p<0.001), greater tumour necrosis factor (TNF) inhibitor (p<0.001, OR=1.50; CI, 1.14, 1.97) and use methotrexate/sulfasalazine (p<0.001, OR=2.25, CI [1.57, 3.23]). Patients with enthesitis were less likely to be male (p<0.001, OR=0.57; CI, 0.43, 0.75) and have peripheral arthritis (p<0.001, OR=2.35; CI, 1.47, 3.75), greater functional impairment (p<0.001, OR=1.91; CI, 1.43, 2.55) and higher ESR/CRP levels (p<0.001). Patients with plantar fasciitis and/or Achilles’ tendonitis on examination were less likely to male (p<0.001 OR=0.57; CI, 0.43, 0.75), to have significant functional impairment (p<0.001), to be using TNF inhibitors (p<0.001, OR=1.48; CI 1.13, 1.93) and to be using either sulfasalazine or methotrexate (p<0.001, OR=1.86, CI, 1.30, 2.67). HLA-B*15 (p=0.03, OR=1.84; CI, 1.05, 3.21) and HLA-B*37 (p=0.04, OR=3.00; CI, 1.03, 8.74) were marginally increased in frequency in those with peripheral arthritis on examination compared with those without.Conclusion There was a higher prevalence of peripheral musculoskeletal manifestations in women with AS, with significant impact on physical function and greater use of methotrexate or sulfasalazine and TNF inhibitors and enrichment for certain non-HLA-B27 HLA-B alleles.